Early surgical abortion: Safe and effective. (April 2013) - Kara, Fatih; Dogan, Nasuh Utku; Bati, Serap; Demir, Senay; Durduran, Yasemin; Celik, Cetin
ABSTRACT Objectives To evaluate patients' characteristics and complications of surgical abortion performed at an early gestation, compared to later gestations. Methods A total of 4310 women with unintended pregnancies attending the family planning unit of a government maternity hospital in Konya, Turkey, were included retrospectively. Abortions were carried out from 6 weeks' up to 10 weeks gestation. Results The gestational age in 62% of the cases was between 6 weeks and 6 weeks + 6 days. Only 8.5% of the 4310 women had used a modern contraceptive method, and 16% had had a surgical abortion for an unplanned pregnancy previously. These women were younger, had more siblings, and a shorter time had elapsed since their last pregnancy when compared to women who never had an abortion. There were four failures (0.09%). The rate of retained products of conception (RPCs) was 1.9% in women aborted between six and six + 6 weeks' gestation, and 6.2% (p < 0.001) in those aborted later. Women who had had a surgical abortion previously more often had RPCs than those who never had (16% vs. 1%, respectively, p < 0.001). Of the 151 women with RPCs, 65 (43%) had been using an intrauterine device prior to surgical abortion. Conclusion Early surgical abortion (at six-six+ 6 weeks' gestation) generates few complications. Delaying surgical abortion until a somewhat later gestation causes complication rates (particularly RPCs) to increase.